Exploring the Drivers of Second-Generation South Asian American Eating Behaviors Using a Novel Qualitative Methodology: Virtual Free-Listing Informed Mind-Mapping. (7th June 2021) - Ali, Shahmir; Gupta, Srishti; Hanif, Channan; Tariq, Maham; Vasquez-Lopez, Xilonen; Penikalapati, Rushitha; Parekh, Niyati; Merdjanoff, Alexis; DiClemente, Ralph
Abstract: Objectives: South Asian Americans (SAAs) face a growing non-communicable disease burden, however the behavioral contributors to health disparities experienced by second-generation South Asians remain under-explored. The aim of this study was to identify major drivers of the foods typically eaten by second-generation SAAs. Methods: Between October-November 2020, second-generation SAAs aged 18–29 years old were recruited to conduct virtual video-conferencing-based interviews using a novel qualitative methodology which integrated free-listing and ranking, mind-mapping, and discussion-based exercises. Ranked free-lists were quantitatively analyzed to identify salient drivers of eating behaviors, while the USDA socio-ecological model was used to inform a semi-inductive thematic analysis of interview transcripts. A network analysis was conducted by quantifying connections made across participant mind-maps. Results: Overall, 32 participants (53% female, 22.4 mean age) were interviewed in the study. Thirty-five distinct eating behavior drivers were identified in the free-listing data; those with the highest saliency scores (unadjusted for ranking) were 1 ) family, 2 ) friends, 3 ) taste, and 4 ) health; when adjusted for participant rankings, the most impactful drivers were 1 ) taste, 2 ) family, 3 ) health, and 4 ) friends. In applying the USDA socio-ecological model, individual-level drivers included personal capacity to cook, convenience in accessing certain foods, cost, emotional state, and preferences regarding taste or novelty of non-South Asian foods. Setting-level drivers included specific daily activities (e.g., socializing, working), people (e.g., family, roommates), and places (e.g., workplaces, religious institutions). Notably less sector-level drivers were identified but included interacting with the healthcare sector or social media. Norm-level drivers included South Asian cultural background, religious background, and priorities regarding health and vegetarianism informed by values outside of religion. Conclusions: Complex, interconnected, and multi-level drivers were identified motivating second-generation SAAs eating behaviors. Findings highlight the need to distinguish these drivers from first generation SAAs to better design interventions to improve health of second-generation SAAs. Funding Sources: N/A.